Political Alienation, Rurality and the Symbolic Role of Swedish Wolf Policy. Issue 11 (2nd November 2017) - Eriksson, Max
ABSTRACT: Attitudes towards wolf policy are likely to be driven by perceived differences in political power between urban and rural groups. Using Swedish survey data collected in 2014 and structural equation modeling, I evaluated the effects of political alienation. Political alienation mediated the effect of having an urban or rural place of residence on attitudes towards wolf policy. Politically alienated individuals also preferred more extreme policy options than other respondents, while being less likely to approve of the current wolf policy in Sweden. These findings suggest that political alienation drives attitude polarization in wolf related social conflicts. Awareness of these underlying power asymmetries could possibly increase both policy legitimacy and management efficiency. This highlights the importance of accounting for social context in relation to policy-making and conservation efforts related to wolves.